2004
DOI: 10.1038/sj.gt.3302405
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gene expression in mice muscle by in vivo electrically mediated siRNA delivery

Abstract: Owing to their capacity to induce strong, sequence-specific, gene silencing in cells, short interfering RNAs (siRNAs) represent new potential therapeutic tools. This development requires, however, new safe and efficient in vivo siRNA delivery methods. In the present technical report, we show that electrically mediated siRNA transfer can suppress transgene expression in adult mice muscles. Using electropulsation for siRNA delivery opens the way for a targeted gene silencing on a broad range of tissues. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 45 publications
2
67
0
Order By: Relevance
“…25 This physical technique has been previously used by different groups including ours to locally deliver siRNAs in various tissues. [29][30][31][32][33][34][35][36] As reported previously we observed that the electrical treatment itself had no detectable effect on tumor growth. Takahashi and coworkers 23 recently found that EP following injection in mouse melanoma tumors slightly improved the uptake of a plasmid encoding luciferase and subsequently attempted this approach for treatment of the tumors with siRNAs or plasmids encoding shRNAs.…”
Section: Rna Extraction and Quantitative Real-time Pcrsupporting
confidence: 61%
See 2 more Smart Citations
“…25 This physical technique has been previously used by different groups including ours to locally deliver siRNAs in various tissues. [29][30][31][32][33][34][35][36] As reported previously we observed that the electrical treatment itself had no detectable effect on tumor growth. Takahashi and coworkers 23 recently found that EP following injection in mouse melanoma tumors slightly improved the uptake of a plasmid encoding luciferase and subsequently attempted this approach for treatment of the tumors with siRNAs or plasmids encoding shRNAs.…”
Section: Rna Extraction and Quantitative Real-time Pcrsupporting
confidence: 61%
“…32 A 15 mm 2 part of the animal was observed, which was suitable to observe the whole tumor. Camera was driven by the MetaVue software 2.6 (Molecular Devices Corporation, Downington, PA, USA) from a Dell computer.…”
Section: Non-invasive Stereomicroscopy Fluorescence Imaging In Live Amentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear how far along a muscle, genes could be silenced; in one study images show silencing for at least 1 cm. 99 Silencing persisted without diminution for 11 days with some silencing still evident 23 days after treatment. Hydrodynamic injection of siRNAs into a peripheral vein of a mouse, rat or monkey limb that had been transiently isolated by reducing blood flow to and from the limb via a tourniquet led to the efficient silencing of a coinjected luciferase reporter plasmid.…”
Section: Musclementioning
confidence: 99%
“…Although multiple studies have used shRNA-encoding viral vectors to transduce muscle cells in vivo, only a few studies have delivered synthetic siRNAs into skeletal muscles either using electrical stimulation 98,99 or localized hydrodynamic injection; 82 however, none of these studies have used siRNAs to investigate siRNA therapy in a disease model. Electrical stimulation was used to deliver previously injected siRNAs into muscle cells to silence reporter genes, such as luciferase and eGFP or an endogenous gene (GAPD).…”
Section: Musclementioning
confidence: 99%